Effect of carbaryl (carbamate insecticide) on acetylcholinesterase activity of two strains of Daphnia magna (Crustacea, Cladocera). Issue 11 (1st November 2016) - Toumi, Hela; Bejaoui, Mustapha; Touaylia, Samir; Burga Perez, Karen F.; Ferard, Jean François
ABSTRACT: The present study was designed to investigate the effect of carbaryl (carbamate insecticide) on the acetylcholinesterase activity in two strains (same clone A) of the crustacean cladoceran Daphnia magna . Four carbaryl concentrations (0.4, 0.9, 1.8 and 3.7 µg L −1 ) were compared against control AChE activity. Our results showed that after 48 h of carbaryl exposure, all treatments induced a significant decrease of AChE activities whatever the two considered strains. However, different responses were registered in terms of lowest observed effect concentrations (LOEC: 0.4 µg L −1 for strain 1 and 0.9 µg L −1 for strains 2) revealing differences in sensitivity among the two tested strains of D. magna . These results suggest that after carbaryl exposure, the AChE activity responses can be also used as a biomarker of susceptibility. Moreover, our results show that strain1 is less sensitive than strain 2 in terms of IC50-48 h of AChE activity. Comparing the EC50-48 h of standard ecotoxicity test and IC50-48 h of AChE inhibition, there is the same order of sensitivity with both strains.